Rhabdoid meningioma with a history of Budd-Chiari syndrome: a case report and review of the literature - Zeng, Ying; Zhang, Jing; Jian, Wei; Zhang, Yong; Yang, Ying; Li, Rongqing; Fu, Qiaofen (Frontiers in Oncology, 2023)
Background Rhabdoid meningioma and Budd-Chiari syndrome are both extremely rare, and there is no report describing the two diseases occurring in the same patient thus far. Herein, we showed an unusual case of rhabdoid meningioma with a history of Budd-Chiari syndrome. Case presentation The man was found to have abnormal liver function during physical examination in 2016 at 36 and was not paid attention to it. In 2019, he went to Beijing YouAn Hospital Affiliated to Capital Medical University for the decompensation of cirrhosis and was diagnosed with Budd-Chiari syndrome, subsequent angiography of the inferior vena cava combined with balloon dilatation were performed, the anticoagulation and hepatoprotective therapy were performed for a long time. When he turned 40 who had magnetic resonance imaging (MRI) that showed a left frontotemporal lobe space-occupying lesion, and postoperative pathological examination confirmed rhabdoid meningioma. He underwent surgery and postoperative adjuvant radiotherapy, but then he developed severe psychiatric symptoms and eventually succumbed to a lung infection two months after treatment. Conclusions Budd-Chiari syndrome and Rhabdoid meningiomas are both extremely rare diseases. To the best of our knowledge, there is no report that the two rare diseases occurred in the same patient, and this is the first case. However, whether there is any link between the two diseases is unclear, more researches are needed to confirm it in the future.